"Delivering the Secret Sauce": Culture and Identity in a Corporate Merger. Issue 1 (18th January 2018) - DORNFELD, BARRY
Abstract : This case study explores work around a merger designed to bring together two firms of different scale, history, and identity in the hospitality industry – a large global conglomerate purchasing a small American boutique brand – while keeping the boutique company's customer‐ and design‐centric culture. It looks at mergers as salient situations for surfacing issues around organizational culture, as companies often come together across multiple differences and brings culture to the surface. CFAR, a management consulting firm, was brought in to understand the cultural differences and challenges the merger created, and help build bridges between the two companies to sustain the boutique's culture in the service of business performance and growth.